Peculiarities of Personality of the Pupils in Adult School - Beresnevičienė, Danguolė (Acta Paedagogica Vilnensia, 1996)
The number of pupils in the adult schools is constantly diminishing – from 12602 in 1989/90 school year to 5873 in 1992/1993 school years. The number of adult schools during that period of time was reduced from 61 to 30. In order to clarify possible reasons for that, a survey was conducted with 250 pupils of 10th, 11th.and 12th forms of adult school. The results showed that pupils of adult school have difficulties of adaptation in their peer group. Self-evaluation of pupils depends on their popularity among the peers. Most popular girls have a higher level of self-esteem, most popular boys – a lower level. Academic aspirations of the pupils of adult school become more realistic as they grow older.
Keywords: Adult education; adult schools; difficulties of adaptation; peer group.